Zinc alters excitatory amino acid neurotoxicity on cortical neurons - Koh, JY (J Neurosci, 1988)
Recent studies have suggested that large amounts of free zinc may be coreleased during excitatory synaptic transmission at glutamatergic synapses, and may act postsynaptically to decrease actions mediated by N-methyl-D-aspartate (NMDA) receptors, while often increasing neuroexcitation mediated by quisqualate receptors. The present study examined the ability of zinc to alter excitatory amino acid (EAA) neurotoxicity. Murine cortical cell cultures were exposed to EAAs for 5 min in defined solutions, and neuronal cell injury was examined the following day both morphologically and by lactate dehydrogenase assay. Inclusion of 30–500 microM zinc in the exposure solution produced a zinc concentration-dependent, noncompetitive attenuation of NMDA- induced neuronal injury, with an ED50 of about 80 microM. In contrast, zinc produced the same concentration-dependent potentiation of quisqualate neurotoxicity; and with 500 microM zinc, a small potentiation of kainate neurotoxicity was suggested. The effect of zinc on the neurotoxicity of the broad-spectrum agonist glutamate was consistent with these effects on specific agonists, as well as with a previous study showing that glutamate neurotoxicity normally depends predominantly on NMDA-receptor activation. Zinc produced a concentration-dependent reduction in glutamate-induced neuronal injury in a fashion similar to that seen with NMDA, but less effectively. In addition, despite this overall protective effect, zinc paradoxically increased the glutamate-induced destruction of nicotinamide adenine dinucleotide phosphate diaphorase (NADPH-d)-containing neurons, a subpopulation that was shown in the preceding paper (Koh and Choi, 1988) to exhibit resistance to NMDA receptor-mediated neurotoxicity, and vulnerability to non-NMDA receptor-mediated neurotoxicity.(ABSTRACT TRUNCATED AT 250 WORDS)